Flexible electroluminescent panels - Vlaskin, V.I.; Vlaskina, S.I.; Koval, O.Yu.; Rodionov, V.E.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Recently developed ac ZnS-powder electroluminescence (EL) devices have
flexibility (thickness is about 60 µm) and can be multisegment, multicolor, as well as
rolled and bent. All colors (white, blue, blue-green, green, and orange) have been
investigated for improvement of their operational characteristics. Many factors including
the type of phosphor, formation method, contacts, initial input power (peak voltage and
frequency), type of input power, and environment safety which define the panel's
properties are discussed.